توظيف تقنية العصف الذهني في تنمية الابداع: دراسة استطلاعية لآراء عينة من موظفي المديرية العامة للتربية في محافظة نينوى - امال سرحان سليمان الطائي (PROSPECTIVE RESEARCHES, 2023)
Brainstorming is a contemporary managerial concept on which creativity process relys. Through individual thinking style and mental behavior with actions within work environment, a matter which is reflected on employees’ performance, quality of their performance, creativity and excellence in the researched organization. Hence the researcher tries to provide a conceptual framework and explains its importance for both organizations and its employees. The practical framework includes describing the sample of research (General Directorate of Education in the province of Ninevah), and identifying the correlation and regression between search variables for both brainstorming and the development of creativity for the employees of general Directorate. Generally the research attempts to answer the following questions:  Can brainstorming be considered as a guide for employee in General Directorate for Education in the province of Nineveh to achieve creativity among individuals working in the research sample organization?  Is there a clear perception among managers in the organization under research about the impact of brainstorming?  How can the adoption of brainstorming surveyed in the organization under research? Finally, according to the conclusions of the research, a number of suggestions which go along with these findings are made.